(3TQM GddeY aj Yde GdMSGHs - (3eMeO Hf eMeO Hf CMeO GdZRGd GdOeTbqj, HOQ GdOjf, GdTgjQ HSHW GdeGQOjfj , J (B912 (3g` s; (3TgGH GdOjf CMeO Hf eMeO Hf YeGO GdOjf Hf Ydj GdefUhQj GdSdej, GHf GdgGFe,J (B815 (3g` s ((3eOQSI GdeQLGfjI s)
(3ChdgG (B:s
(3hHYO ajbhd eMeO Hf eMeO Hf CMeO SHW GdeGQOjfi gPG JYdjb eNJUQ LYdJg JhVjMkG Ydi GdebOeI GdeSeGI HGddeY ai Yde GdMSGH s
(3BNQgG (B:s
(3hCbSe GdMGUd ddChd hgh SJhf Ydi GdMGUd GdKGfi hgh NeSI YTQ JeJ s
(3GdfSNI HgG MhGTs
(3fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdQjGVjGJs